The Cervical Cancer (CC) Epidemiology and Human Papillomavirus (HPV) in the Middle East - Jalil, Abduladheem Turki; Karevskiy, Aleksandr (International Journal of Environment, Engineering & Education, 2020)
Viral infections contribute 15–20 percent of all human cancers as a cause. Oncogenic virus infection may spur various stages of carcinogenesis. For several forms for HPV, about 15 associated with cancer. Following successful test techniques, cervical cancer remains a significant public health issue. Prevalence and mortality of per geographic area of cervical cancer were vastly different. The fourth most common cause of death from cancer among women is cervical cancer (CC). Human papillomavirus (HPV) infection in the cervix is the most significant risk factor for forming cervical cancer. Inflammation is a host-driven defensive technique that works rapidly to stimulate the innate immune response against pathogens such as viral infections. Inflammation is advantageous if it is brief and well-controlled; however, it can cause adverse effects if the inflammation is prolonged or is chronic in duration. HPV proteins are involved in the production of chronic inflammation, both directly and indirectly. Also, the age-specific prevalence of HPV differs significantly. Two peaks of HPV positive in younger and older people have seen in various populations. A variety of research has performed worldwide on the epidemiology of HPV infection and oncogenic properties due to specific HPV genotypes. Nevertheless, there are still several countries where population-dependent incidences have not yet identified. Additionally, the methods of screening for cervical cancer differ among countries.